2023
DOI: 10.1017/s0047279423000090
|View full text |Cite
|
Sign up to set email alerts
|

Social Policy Expansion and Retrenchment in Latin America: Causal Paths to Successful Reform

Abstract: The literature on social policy expansion and retrenchment in Latin America is vast, but scholars differ in how they explain outcomes, arriving at different conclusions about the role of democracy, left parties, favorable economic conditions, and social movements. What can welfare state developments since the end of the commodity boom teach us about the theoretical power of these arguments? This paper engages this question, seeking to explain recent incidents of successful social policy reform in 10 presidenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(85 reference statements)
0
0
0
Order By: Relevance
“…We chose the control variables based on theoretical justifications and empirical evidence. Changes in social spending can be caused by numerous factors, such as: an increase in a country's wealth and individual income and consumption may increase the political system's resources to finance social welfare (Lamartina and Zaghini, 2011; Myles and Quadagno, 2002; Wilensky, 1975) an increasing electoral competition which may cause opposition and government to back social policy expansion to expand their electoral pool of support to win elections (Altman and Castiglioni, 2020; Ewig, 2016; Garay, 2016; Niedzwiecki and Pribble, 2023) the ideological orientation of the party in the executive, precisely thanks to left-of-center parties (Sirén, 2021). Huber and Stephens (2012) found that left political strength is a determinant of the region's social security and health expenditure. We incorporate four controls 4 in the linear regression analyses to take into account the explanatory effects of the four items mentioned above: Country's wealth (GDP per capita), individual income and consumption (GDP per capita growth), electoral competition (index of effective competition proposed by Altman and Perez-Liñan (2002) 5 , and an additive index to measure the strength of the left combining the orientation of the party of the executive, and the center-left seat share in the lower house (both according to Coppedge's coding rules) (Huber and Stephens, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the control variables based on theoretical justifications and empirical evidence. Changes in social spending can be caused by numerous factors, such as: an increase in a country's wealth and individual income and consumption may increase the political system's resources to finance social welfare (Lamartina and Zaghini, 2011; Myles and Quadagno, 2002; Wilensky, 1975) an increasing electoral competition which may cause opposition and government to back social policy expansion to expand their electoral pool of support to win elections (Altman and Castiglioni, 2020; Ewig, 2016; Garay, 2016; Niedzwiecki and Pribble, 2023) the ideological orientation of the party in the executive, precisely thanks to left-of-center parties (Sirén, 2021). Huber and Stephens (2012) found that left political strength is a determinant of the region's social security and health expenditure. We incorporate four controls 4 in the linear regression analyses to take into account the explanatory effects of the four items mentioned above: Country's wealth (GDP per capita), individual income and consumption (GDP per capita growth), electoral competition (index of effective competition proposed by Altman and Perez-Liñan (2002) 5 , and an additive index to measure the strength of the left combining the orientation of the party of the executive, and the center-left seat share in the lower house (both according to Coppedge's coding rules) (Huber and Stephens, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…an increasing electoral competition which may cause opposition and government to back social policy expansion to expand their electoral pool of support to win elections (Altman and Castiglioni, 2020; Ewig, 2016; Garay, 2016; Niedzwiecki and Pribble, 2023)…”
Section: Methodsmentioning
confidence: 99%